Cyberdefense and cybersecurity in Peru: reality and challenges regarding the ability of the armed forces to neutralize cyberattacks that threaten national security. - Quevedo Lezama, Christian Rafael (2023)
Cyberdefense and cybersecurity have become pillars of maintaining any country's stability and normal functioning; therefore, they are considered vital areas within strategic studies. Unfortunately, faced with this demand, Peru has not been able to develop this sector. Currently, the country does not have an investment aimed at promoting security systems and cyber defense. Although the Latin American region has little impact on large-scale cyber conflicts, it is essential to note that national security could be violated if it does not level with current demands. The methodology used for the development of the present was delimited in this documentary review, concluding that to achieve efficient cyber defense and cybersecurity strategies, a system is necessary that allows the integration and cooperation of the public, private and military sectors, which makes possible the union of isolated forces to achieve the objectives of national security.